ВОПЛОЩЕНИЕ КАТЕГОРИИ УСЛОВИЯ В ВОЛШЕБНОЙ РУССКОЙ СКАЗКЕ - Чергинская, И.А. (SCIENCE and SOCIETY, 2020)
The article discusses the specifics of complex sentences with conditional relationships and presents tasks that can be used to study the topic “Conditional relationships in a complex sentence”. Work on complex sentences with conditional relationships was based on the use of a fairy-tale by A.S.Pushkin "The Tale of KingSaltan."
Keywords: Russian language; conditional relations ship; compound sentence; magic Russian fairy tale; unions; study; educational process